PENGARUH DIGITAL MARKETING, RELATIONSHIP MARKETING DAN PROMO DISKON TERHADAP MINAT BELI KONSUMEN PADA TOKO CLOTHING BENGKULU - Saputra, Rangga; Onsardi, Onsardi (Yayasan Insani Mandiri Santani, 2024)
The aim of the research is to determine the influence of digital marketing, relationship marketing and discount promotions on consumer buying interest in Bengkulu clothing stores. And to find out which factors most dominantly influence purchasing decisions.This research used quantitative methods on 170 respondents. The population used in this research was Bengkulu Clothing Shop consumers and the sampling in this research used a non-probability sampling technique. The research results and hypotheses show that Digital Marketing, Relationship Marketing and Discount Promos Affect Consumer Buying Interest in Bengkulu Clothing Stores. have a partial or simultaneous positive effect on consumer buying interest.Keywords: Digital Marketing, Relationship Marketing, Discount Promos and Purchase Interest